2015
DOI: 10.1111/jbi.12669
|View full text |Cite
|
Sign up to set email alerts
|

Ecological traits shape genetic diversity patterns across the Mediterranean Sea: a quantitative review on fishes

Abstract: Aim We set out to identify the determinants of the variation in genetic diversity among fish species and test whether multi-species genetic diversity is randomly distributed in space.Location Mediterranean Sea.Methods We collected genetic diversity data from 39 published studies on Mediterranean fishes (31 species) along with the spatial coordinates of the sampling sites. We focused on microsatellite heterozygosity (151 data points) and mitochondrial haplotype diversity (201 data points). We used linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 107 publications
4
29
0
Order By: Relevance
“…However, historical signals of demographic processes can weaken the relationship between census and effective population size, and thus the relationship between abundance and heterozygosity (Frankham, ). For example, range expansions or population bottlenecks can lead to reduced genetic diversity in marginal or founder populations, and consequently to decoupling from contemporary census population size (Banks et al, ; Charlesworth, ; Dalongeville, Andrello, Mouillot, Albouy, & Manel, ; Excoffier & Ray, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, historical signals of demographic processes can weaken the relationship between census and effective population size, and thus the relationship between abundance and heterozygosity (Frankham, ). For example, range expansions or population bottlenecks can lead to reduced genetic diversity in marginal or founder populations, and consequently to decoupling from contemporary census population size (Banks et al, ; Charlesworth, ; Dalongeville, Andrello, Mouillot, Albouy, & Manel, ; Excoffier & Ray, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found strong relationships between ecological traits and genetic diversity at broad phylogenetic scales (e.g., across phyla; Romiguier et al, ); whether such patterns are also exhibited by more closely related species with similar life history traits remains equivocal (Ellegren & Galtier, ; Romiguier et al, ; Singhal, Huang, et al, ). Additionally, there is some evidence that microhabitat preference can limit dispersal and reduce within‐population genetic diversity (Brouat, Chevallier, Meusnier, Noblecourt, & Rasplus, ; Brouat, Sennedot, Audiot, Leblois, & Rasplus, ; Dalongeville et al, ; Khimoun et al, ; Pianka, ; Rabosky, Cowan, Talaba, & Lovette, ), but studies combining genome‐wide diversity estimates with ecological traits at the community level are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of biodiversity at the local scale is critically dependent on the persistence of populations, influenced by self‐recruitment and propagule supply that are, to a wide extent, species‐specific processes. Connectivity itself, which depends on ocean circulation, life history traits, local population dynamics and spatial distribution of populations (Jonsson & Watson, ), is largely determined by specific population processes, and it is often inferred, for single species, at the metapopulation level (Dalongeville, Andrello, Mouillot, Albouy, & Manel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the design (location and size) of a robust MPA network should be supported by connectivity estimates for all the species of a given community to identify a consensus network which ensures enough connectivity to multiple species with different life history traits (Costantini, Ferrario, & Abbiati, ; Dalongeville et al, ; Jonsson & Watson, ; Pascual et al, ; Shanks, Grantham, & Carr, ). Recently, Melià et al () showed a novel methodological framework to synthesize species‐specific results into a set of community connectivity metrics and showed that spatiotemporal variation in magnitude and direction of the connections and interspecific differences in dispersing traits are key factors structuring community connectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation